Wilson’s Disease and Autoimmune Hepatitis Coexistence: A Cause of Diagnostic Delay - Mohammed G Mudawi; Salma Barakat MD; Elhadi M Awooda (Sudan Journal of Medical Sciences)
This case report describes a 27-year-old housewife who presented with a progressive and insidious onset of abdominal distension, loss of appetite, and fatigue which started 3 months before her presentation. The physical assessment showed moderate ascites and small liver size, and no other peripheral evidence of chronic liver disease was observed. A diagnosis of liver cirrhosis and was confirmed by investigations and imaging, where ascites responded well to therapy with diuretics. Investigations for the cause of cirrhosis was established through the diagnosis of autoimmune hepatitis, and she was started on steroids and azathioprine with partial improvement in liver biochemistry. She presented 8 months later with neuropsychiatric symptoms in the form of slurred speech and difficulty walking. Accordingly, Wilson’s disease was suspected to be the cause and further investigations confirmed this. A chelating agent, D penicillamine, was added to her immunosuppressive treatment. Nine months later she showed slow improvement in her neurological symptoms and was referred for assessment for liver transplantation. Wilson’s disease, although rare, should be suspected in patients with decompensated liver disease. The dominance of clinical and epidemiological features of autoimmune hepatitis as a common causative pathology for chronic liver disease in young and middle-aged ladies may hide the presence of other serious different pathologies such as Wilson’s disease.